A multistage solar still with photovoltaic panels and DC water heater using a pyramid glass cover enhanced by external cooling shower and PCM. Issue 7 (24th June 2021) - Al‐Hamadani, Ali A. F.; Yaseen, Altaf Hameed
Abstract: A novel multistage solar desalination system with a photovoltaic heater was manufactured. The base of the down basin of the solar still had a layer of paraffin wax with a mass of 13 kg as a phase change material. The system has been studied to evaluate the enhancement of freshwater. Saltwater was heated by solar radiation and by a direct current water heater. The surfaces of condensation vapor, such as the pyramid glass cover and lower surface of two stacked trays, were designed. This is to improve the productivity of freshwater by decreasing the resistance of condensation. The high temperature of the glass cover is modified by using a cooling water shower, especially at the highest intensity. The study includes parameters, such as cooling water shower flow rate, down basin water level, and the effect of the heater. It is observed that the novel solar desalination is proportional to solar radiation, paraffin wax, the heat input from a heater, cooling water shower flow rate, and down basin water level. The Multiple Stage Effect Photovoltaic Heater (MSEPVH) can produce 15 L/day of distilled water. The excellent flow rate of cooling water, the total freshwater, and the efficiency of MSEPVH for the optimal day were mathematically and experimentally determined.